Analysis of Mental Health Risk Factors Among Adolescents in the Digital Era and Their Implications for Public Health Policy - Muti Atun Nafi’ah (PT. AVID MEDIA INDONESIA, 2026)
Adolescent mental health has become an increasing global concern in the digital era, characterized by rising levels of depression, anxiety, and stress influenced by complex biopsychosocial and digital factors. This study aims to analyze the prevalence of adolescent mental health problems, identify key risk factors, and examine their implications for public health policy. A quantitative approach with an explanatory design was employed, involving adolescents as research participants. Data were collected through structured questionnaires measuring mental health conditions, digital risk factors, and social-environmental variables. The data were analyzed using descriptive statistics and multiple regression analysis to determine the influence of each factor on mental health outcomes. The results indicate that adolescent mental health conditions are in the moderate to high category, with digital risk factors such as screen time, social comparison, and cyberbullying having the strongest influence. Social and environmental factors, including peer pressure and socioeconomic stress, also significantly contribute to mental health problems, while family support acts as a protective factor. The findings highlight that the impact of digital technology is context-dependent and interacts with broader social determinants. In conclusion, adolescent mental health requires integrated, evidence-based public health interventions that address digital behavior, strengthen social support systems, and reduce structural inequalities to promote long-term well-being.